Low genetic diversity of Anaplasma marginale in calves in an endemic area for bovine anaplasmosis in the state of São Paulo, Brazil - Silva, Jenevaldo Barbosa da [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier B. V., 2015)
Major surface protein 1a has been used as a marker for genetic stability in identifying geographical isolates of Anaplasma marginale. We conducted a longitudinal study to ascertain the genetic diversity of A. marginale in a dairy cattle herd with a history of clinical anaplasmosis. A total of 20 calves were evaluated every 3 months, from birth to 1 year of age. They were evaluated using blood smears, IFAT, ELISA, and qPCR. Additionally, samples positive for the msp1a gene using nPCR were sequenced. The detection of A. marginale ranged from 20 to 90% using blood smears, 20-80% using ELISA/IFAT, and 15-100% using qPCR. We found evidence that suggested transplacental transmission of A. marginale in 15% (3/20) of the calves based on qPCR and 20% (4/20) based on blood smears. Additionally, these four animals were A. marginale ELISA/IFAT-positive. The A. marginale strains found were α-β(3)-Γ (n=7), α-β(2) (n=1), and α-β(2)-190-Γ (n=1). The new MSP1a tandem repeat 190 was described. The results showed that the genetic diversity of A. marginale in a group of calves up to 1 year of age from Taiaçu (SP) was low, with only three different strains identified, showing the microsatellite genotype E. Eighty percent of the animals evaluated had clinical signs of bovine anaplasmosis and were treated using oxytetracycline and imidocarb dipropionate. Additionally, it was found that 30% (6/20) and 10% (2/20) of the animals required a second and third treatment, respectively, based on clinical signs. Four animals infected with the α-β(3)-Γ strain died, showing that this strain is also involved in the clinical anaplasmosis cases in Brazil.
Keywords: Bovine anaplasmosis; Genetic diversity; Msp1a; Α-β(3)-γ